Draft Annual Plan Proposal 1990-91 (Volume-I) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1990)
The Andaman and Nicobar Group of Island-comprise 072 Islands including 266 rocks) with a total geographical area of 0249 Sq. Km They are situated between 6 and 14 North latitude and 92° and 94° East longitude in the Bay of Bengal with the 10° channel separating the Andaman group of islands from the Nicobar group. The islands lie in a long, narrow, broken chain approximately North South, in an are. Port Blair, where the headquarters of this territory's Administration is located, is 1255 Km away from Calcutta and 1191 Km from–Madras Calcutta and Madras are the two ports through which the islands maintain communication with the mainland. The A & N Islands constitute the most isolated part of India, surrounded by vast stretches of sea in every direction.
Introduction, Sectoral Review and Statements
Andaman and Nicobar Administration
Keywords: Andaman and Nicobar Administration; Introduction; Sectoral Review and Statements; General; Planned development; Anti Poverty Programme; Resources position; The Andaman and Nicobar Group of Island; The islands have a tropical climate; Large scale influx of people into this Territory; Administration Andaman and Nicobar Islands; Agriculture of any importance has developed; Planned development in A & N Islands; Generation of additional gainful employment; Recourses Position